IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA PEKANBARU TENTANG PAJAK REKLAME TAHUN 2015-2016 - Laini, Nisa; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The city of Pekanbaru as a metropolis has a lot of strategic places to install billboards, both billboards and boards and even more sophisticated that is a giant Laser Compact Disk (LCD) screen or also called megatron billboard. Currently, many unresolved billboard issues, ranging from illegal billboard issues that do not have a license until advertisement tax acceptance, so as to reduce the Original Regional Income.The purpose of this study is to know the implementation of Pekanbaru City Government Policy About Reklame Tax Year 2015-2016 and to know the obstacles in Policy Implementation Pekanbaru City Government About Reklame Tax Year 2015-2016. The method used in this research is Qualitative Research Method. The subjects in this study are the Head of Tax Division, Head of Sub Division of Advertising Tax, Ground Water, Street Lighting and Non-Metal Mineral, Sub Division Staff of Advertisement Tax, Ground Water, Street Lighting and Non-Metal Mineral and Advertisement Users in Soekarno-Hatta street Kecamatan Tampan.The result of the research shows that the implementation of Pekanbaru City Government Policy on advertisement tax of 2015-2016 can be said to be less well, firstly, the communication is not good enough. Secondly, the resources in the implementation of policy of this regulation is still lacking, the lack of human resources and facilities supporters in the implementation of the policy of this regulation. Third, the bureaucratic structure in the implementation of the policy of this law has not gone well. Fourth, in terms of disposition itself has gone well. So, it can be concluded that the implementation of policy Perda Pekanbaru City No. 4 of 2011 About Reklame Tax has not gone well. The obstacles in Pekanbaru City Government Policy Implementation on the advertisement tax of 2015-2016 are the insufficient number of supervisory officers from Bapeda, the limited operational vehicle and the lack of public awareness to manage the advertisement permit.Keywords: Implementation, Advertising Tax